Blockchain Revolution: How Decentralization will Change the World - Kuku, David (My University, 2023)
Blockchain technology has been gaining momentum in recent years as a potential disruptor of traditional centralized systems. Its decentralized nature, immutability, and security features have the potential to revolutionize various industries, from finance to healthcare, supply chain management, and beyond. This article explores how blockchain technology works, its core features, and how it can enable decentralization. It also examines some of the key benefits of blockchain, such as increased transparency, security, and efficiency, and highlights some of the challenges and limitations that need to be addressed for widespread adoption. Finally, the article provides insights into how blockchain technology is already being used in real-world applications and its potential to transform society as we know it
Keywords: Blockchain; Revolution; Globalization